(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
In this paper, three binary Ni-13.4 at.% Al/Ni-17.7 at.% Al diffusion couples were first prepared and subjected to homogenization at 1573 K for 18000 s, from which a continuous concentration profile forms. The three diffusion couples were then cooled down for aging at respective temperatures, i.e., 1173, 1123 and 1073 K, for 14400 s. The effect of composition and aging temperature on the aging microstructure was studied in detail by means of different experimental techniques and statistical analysis. The volume fraction, grain size and shape factor of γʹ precipitates in the three diffusion couples were plotted as a function of alloy composition and annealing temperatures. Together with the previously proposed evaluation function in which the phase fraction, grain size and shape factor of γʹ precipitates were chosen as the evaluation indicators, the optimal alloy composition and aging temperature for binary Ni-Al alloys with the best mechanical properties were evaluated, and finally validated by the measured hardness values. The successful demonstration of alloy design in the present binary Ni-Al alloys indicates that the two-step diffusion couple together with the evaluation function for mechanic properties should be of generality for high-throughput screening of optimal alloy composition and heat treatment process in different alloys.